FAKTOR YANG MEMPENGARUHI PERANAN KELOMPOK SIAGA BENCANA UNTUK MEWUJUDKAN KESIAPSIAGAAN MASYARAKAT DI KOTA PADANG - Muhardina Jelita; Zikri Alhadi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
North Padang Subdistrict is a region that is often hit by floods and coastal abrasions, and is a red zone in the earthquake and tsunami disaster. This study discusses the factors that influence the role of the disaster preparedness group during pre-disaster to realize the preparedness of the community in Padang Utara Sub-District. This research uses descriptive qualitative research. Methods in collecting data through interviews and documentation studies. In determining informants using purposive and incidental techniques. The results of this study indicate that disaster preparedness groups in carrying out their roles during pre-disaster are influenced by several factors. Factors that encourage the Disaster Alert Group to play a role are the geographical conditions of the northern Padang sub-districts that are prone to disasters, the existence of programs from the regional government for disaster risk reduction, and the existence of a social humanitarian spirit possessed by members of the Disaster Alert Group. Meanwhile, the inhibiting factor is the absence of operational funds for activities owned by the Disaster Preparedness Group, the absence of facilities and infrastructure for supporting activities, the condition of members who are partly indifferent, and the conditions of the community in the area.